北冰洋西部表层沉积物中生源组分及其古海洋学意义 - 王汝建; 肖文申; 向霏; 陈建芳; 高爱国; 陈荣华; 程振波; 李秀珠; 韩贻兵; 李亮 (2007)
通过对中国首次和第二次北极科学考察在北冰洋西部所采取的66个表层沉积物中生源组分的分析,探讨了该海区表层生产力变化与水团的相互关系。楚科奇海西南部呈现出高的有机碳和生源蛋白石含量,而中部和东部哈罗德浅滩至阿拉斯加沿岸,以及楚科奇海台、北风脊和加拿大海盆表现出低的有机碳和生源蛋白石含量。楚科奇海陆架区表层沉积物以底栖有孔虫为主,丰度低;而楚科奇海台、北风脊和加拿大海盆则以浮游有孔虫占绝对优势,丰度较高。生源组分的分布特征显然与通过白令海峡进入楚科奇海的三股太平洋水和大西洋次表层水相关。楚科奇海西侧沿富营养的阿纳德尔流方向的区域呈现出高的表层生产力。而东侧受寡营养的阿拉斯加沿岸流及阿拉斯加西北沿岸陆源物质输入的影响,呈现出低的表层生产力。北纬75°以北及加拿大海盆受海冰覆盖影响,也表现出最低的表层生产力。而受北大西洋次表层水的影响,楚科奇海陆架外侧高纬海域表现出较高的钙质生物生产力。表层沉积物中Corg/N比值及其分布反映楚科奇海表层沉积物中的有机碳以海洋自身来源为主,且主要受生物泵过程控制。有机碳和生源蛋白石含量呈现高的正相关关系,说明硅藻等浮游植物的初级生产力可能控制着生物泵对碳的吸收和释放。 Biogenic components in total 66 surface sediments,which were taken in the western Arctic Ocean during the First and Second Chinese National Arctic Expedition cruises,are analyzed for probing into the relationship between surface productivity and water masses in area studied.As a result of the investigation,high organic carbon and biogenic opal percentages appear in the southwestern Chukchi Sea.On the contrary,low organic carbon and biogenic opal percentages occur in several areas,including the central Chukchi Sea,Herald Shoal,seacoast of Alaska,Chukchi Plateau,Northwind Ridge and Canada Basin.High foraminiferal abundance emerges in the Chukchi Plateau,Northwind Ridge and Canada Basin where the planktonic foraminifera dominate.Inversely,low foraminiferal abundance comes on the shelf of the Chukchi Sea where the benthic foraminifera dominate.Distribution patterns of biogenic components are associated obviously with three branches of the Pacific Water from the Bering Strait into the Chukchi Sea and the subsurface Atlantic Water.High surface productivity presents in the area of abundant nutrient Anadyr Water in the western Chukchi Sea.Reversely,low surface productivity appears in the areas influenced by scant nutrient Alaska Coastal Water and terrigenous matter input along northwestern Alaska seacoast.Similarly,low surface productivity in the northern area higher than 75°N and Canada Basin is attributed to the long-term sea ice coverage.High calcareous productivity in the outer side of Chukchi Sea Shelf and high latitude is ascribed to the influence of the subsurface Atlantic Water.The Corg/N ratio in surface sediments and its distribution pattern indicate that the organic carbon in surface sediments of the Chukchi Sea mainly originates from marine source and is controlled by biological pump process.High correlative coefficient between organic carbon and biogenic opal shows a closer relationship between organic carbon and diatom.Primary productivity of diatom and other phytoplankton can control the absorption and release of biological pump for carbon. 国家重点基础研究发展规划项目(G200078500);; 国家自然科学基金项目(40321603,40676030,40576029);; 高等学校博士学科点专项科研基金(20040247028)